El ruido original del tango: viaje al centro de la orquesta típica. (Revista Argentina de Musicología, 2018)
During the first decades of the twentieth century, contemporary music turned its attention to timbre as a central parameter of its aesthetic development, introducing noise as a new material. This article tracks how Tango music also incorporated noise as an important characteristic of the genre with the rise of the Orquesta Típica. We argue that this specific instrumental line-up implies an original timbrical invention from which the whole genre does unfold, based on the mixture between bowed strings, piano and bandoneones. The article proposes that at the center of this amalgam between fixed and free tuning instruments, lays the impossibility of a perfectly tuned harmony. This installs great instability at the origin of this timbre, resulting in an orchestra built upon a foundational noise component that will expand its tension into the music. After doing a spectral analysis of this timbre, the article suggests that Tango can be thought of as the expansion of this original noise, this basic disagreement, this unresolved tension.
Keywords: timbre; tango orchestra; noise; tuning; beatings